lHubungan Tingkat Pengetahuan Ibu Terhadap Pemberian MP-ASI Dini Di Pmb Ain Handayani, S.Keb Kota Bekasi - Yusika, Kiki; Bunda, Muntamah (Journal of Midwifery Tiara Bunda, 2022)
Background: Proper administration of MP-ASI not only disrupts the nutritional intake that babies should get, but also interferes with the baby’s digestion because the digestive system is unable to digest or destroy the food. Exclusive breastfeeding coverage for infants 0-6 months in the Midwife Independent Practice M, Amd.Keb, Medan Satria, Bekasi City 2022 is still low. The purpose of this study was to determine the factors of early MP ASI administration in 0-6 months infants in the Midwife Independent Practice M, Amd.Keb, Medan Satria, Bekasi City Work Area 2022. Metode:The design of this study was descriptive analytic with a cross sectional approach. The ample of this study was all mothers who had infants (0-6) months who were in the working area of the Midwife Independent Practice Muntamah, Amd.Keb, Medan Satria, Bekasi City which amounted to 63 people. This study uses univariate, bivariate and multivariate analysis. The results: of the univariate analysis of this study showed that from 63 respondents, almost half (49.2%) had a supportive attitude, more than a portion (54.0%) worked, almost half (44.4%) whose husbands supported and more than partially (61.9%) who gave MP ASI Dini. The results of the bivariate analysis obtained an attitude with p value = 0.001 α α = 0.05, the work of the mother with p value = 0.005 ≤ α = 0.05 and the support of the husband with a value of p = 0.007 ≤ α = 0.05. Conclusion: The results of this study showed the greatest attitude variables associated with early MP ASI administration in infants aged 0-6 months at the Midwife Independent Practice M, Amd.Keb, Medan Satria, Bekasi City in 2022. It is expected that the puskesmas should increase information dissemination through counseling to the community through the role of cadres to increase knowledge about the importance exclusive breastfeeding.